From waste to wealth: recycling the secondary resource from steel ladle as a flux in Si-killed steelmaking process. (14th September 2019) - Bharati, Sanghamitra; Basavaraja, V. M.; Jagadeesha, R. J.; Jagteri, K.; Sah, R.; Prasad, G.; Behl, T.; Manjini, S.
ABSTRACT: With the regulations pertaining to the environment and waste disposal becoming stringent day by day, the steelmaking industry is being compelled to adopt a zero-waste-policy for sustainability. As a consequence, 3R (reduce, reuse and recycle) technique of waste handling has become the most favoured option among the industries. This paper focuses on recycling of slag generated after secondary refining process. Trials were conducted in two stages, namely (a) prevention of dusting phenomenon of Al-killed steel ladle slag to generate lump slag by suitably selecting the ladle covering compound and chemically modifying the slag, and (b) utilisation of the lump slag as a 100% replacement of synthetic slag in Si-killed steel ladles, leading to a reduction in its specific consumption from 1.2 kg/TLS to zero. As a process requirement, specific power consumption, arcing time and degree of desulphurisation were considered as the major parameters for comparing the results using hypothesis test statistical tool.